Learn GCP Cloud Functions in One Hour Video Course - Deza, Alfredo; Deza, Alfredo; Gift, Noah (Pragmatic AI Solutions, 2021)
Get started with Google Cloud Platform (GCP) and Cloud Functions in this one-hour video. Everything you need to know to get up and running quickly using serverless technology from GCP. Topics include: * An introduction to serverless technologies * Create a cloud function, install dependencies, and use different runtimes like Python 3.8 * Debug issues when a cloud function deployment fails * Use Google's Machine Learning offering to do live translations to any language * Enable authentication for your cloud function.